Pengaruh Masukan Kendali Terhadap Hasil Identifikasi Parameter Pesawat Udara Konfigurasi Konvensional Matra Terbang Longitudinal - Eries Bagita Jayanti; Novita Atmasari; Hidayati Mardikasari; Ardian Rizaldi; Fuad Surastyo Pranoto; Singgih Satrio Wibowo (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2019)
Parameter identification is a process to get real characteristics of the motion dynamics of an object which can then be used to build the dynamics model of the object, which has a very high level of validity and accuracy. The modeling process is usually carried out using aircraft input data and the results of existing navigation data recording. From the data, the model parameters are estimated using the simple least square method. In this study, the simulation was carried out by varying the deflection input in the control field and simulation time. The input given to the longitudinal dimension is the deflection of the elevator control field. The results of parameter identification in the Corsair A-7A plane in the longitudinal dimension indicate that the input form 3-2-1 has a smaller error value than using doublet and pulse inputs. This shows that the input form 3-2-1 is most suitable for the longitudinal dimension among the given inputs.